2021
DOI: 10.1038/s41467-020-20269-y
|View full text |Cite
|
Sign up to set email alerts
|

Steroid hormones sulfatase inactivation extends lifespan and ameliorates age-related diseases

Abstract: Aging and fertility are two interconnected processes. From invertebrates to mammals, absence of the germline increases longevity. Here we show that loss of function of sul-2, the Caenorhabditis elegans steroid sulfatase (STS), raises the pool of sulfated steroid hormones, increases longevity and ameliorates protein aggregation diseases. This increased longevity requires factors involved in germline-mediated longevity (daf-16, daf-12, kri-1, tcer-1 and daf-36 genes) although sul-2 mutations do not affect fertil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Loss of function of the C. elegans sul-2 gene (steroid sulfatase, STS) increased the concentration of sulfated steroid hormones, as well as longevity, and improved the phenotype in several C. elegans models of protein aggregation diseases. The same effects were obtained in C. elegans models using STX64, a specific STS inhibitor that also ameliorated the phenotype in a mammalian model of AD [ 157 ].…”
Section: Use Of C Elegans Models Of Alzheimer’s Di...mentioning
confidence: 53%
“…Loss of function of the C. elegans sul-2 gene (steroid sulfatase, STS) increased the concentration of sulfated steroid hormones, as well as longevity, and improved the phenotype in several C. elegans models of protein aggregation diseases. The same effects were obtained in C. elegans models using STX64, a specific STS inhibitor that also ameliorated the phenotype in a mammalian model of AD [ 157 ].…”
Section: Use Of C Elegans Models Of Alzheimer’s Di...mentioning
confidence: 53%
“…Results indicated that STS inhibition may be neuroprotective against neurotoxic amyloid β accumulations in the brain and that this is possibly due to increased DHEA-S availability. Recently, these findings have been supported by a study using Caenorhabditis elegans who have had their STS activity (sul-2) deleted [144]. Loss of steroid sulfation led to a rise in sulphated steroids, increased life span, and inhibited protein aggregation diseases.…”
Section: Future Outlook For Sts Inhibitorsmentioning
confidence: 88%
“…The protein was mixed with 1.0 µL of crystallization solution in the wells. Protein was also incubated on ice for 30 min with sulfatase irreversible inhibitor STX64 (Axon Medchem, Reston, VA, USA) [ 43 , 44 ] with a final inhibitor concentration of 1.0 mM before setting drops. However, the inhibitor did not solubilize well in the protein mixture and precipitated out of solution in the crystallization drops.…”
Section: Methodsmentioning
confidence: 99%